Certification Programme For Sustainable Forest Management - Pudji Muljono (Business and Entrepreneurial Review, 2007)
The article describes about cerlification programme for sustainable forest management. Concern for forest problems has increased dramatically over last decade. Sustainable forest management is an inherent aim of certification. It is the ultimate goal to which certified forest should aspire, but such a goal is reached only through a period of transition, during which management standards are progressively established and fine-tuned. The explicit aim of certification is to improve the quality of forest management so as to reach this goal. The aim of certification systems is to make timber production more ecologically and socially responsible and economically viable by grading sources so that consumers can choose on these grounds. The argument is that environmentally aware consumers will be prepared to pay more for products if they know where these come from and how they have been produced. Higher prices will motivate timber companies to implement sustainable forest management principles. There are certain general principles of sustainability which have been agreed, these include emvironmental sustainability social sustainability and economic sustainability. This article describes focus on certification in context, certification in practice, views on certification, overall trends in the certification debate, the sticky issues differing views that need resolving, and the forest certification programme in lndonesia.